Export Entrepreneurs : Evidence from Peru - Freund, Caroline (2012)
This paper examines firm entry and survival in exporting, and in products and markets not previously served by any domestic exporters. The authors use data on the nontraditional agriculture sector in Peru, which grew seven-fold from 1994 to 2007. They find tremendous firm entry and exit in the export sector, with exits more likely after one year and among firms that start small. There is also significant entry and exit in new markets. In contrast, such trial and error in new products is rare. New products are typically discovered by large experienced exporters and there is increased entry after products are discovered. The results imply that high sunk costs of entry are of concern for product discovery, especially for products that are not consumed domestically. In contrast, the tremendous entry and exit in exporting and in new markets suggests that initial sunk costs are relatively low. The authors develop a model that explains how entrepreneurs decide to export and to develop new export products and markets when there are sunk costs of discovery and uncertainty about idiosyncratic costs. The model explains many features of the data.